Penyuluhan Dan Pemeriksaan Sindrom Ovarium Polikistik Pada Remaja Di Pesantren An Nizam Minas - Nicko Pisceski Kusika Saputra; Munawar Adhar Lubis (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2024)
Polycystic ovary syndrome (PCOS) is a complex condition characterized by increased androgen levels, menstrual irregularities, and/or the presence of small cysts in one or both ovaries. The incidence of PCOS increases every year, including in Riau Province. Therefore, this service is carried out on teenagers, namely female students at the An Nizam Minas Islamic Boarding School, Siak Regency, to see the picture of PCOS in teenagers so that they can change their behavior and attitudes regarding eating patterns and better lifestyles so that it does not interfere with fertility in teenagers if they are diagnosed with PCOS. We intend to provide education regarding PCOS to teenagers and carry out ultrasound examinations on students who are suspected of having PCOS. The indicator of the success of this activity is that there is an increase in students' knowledge regarding PCOS through analysis of pretest and posttest results. Through this activity, publications will be produced in national journals, mass media publications and intellectual property rights. We show that there is an increase in the level of respondents' knowledge about PCOS between before and after the activity.